The power of regret how looking backward moves us forward - Pink, Daniel H (New York Riverhead Books, 2022)
In the Power of Regret, Daniel Pink trains his intellect and wit on a deeply important subject that we've all experienced but few have explored. The stories he tell are fascinating and so are the insights he draws from them. whatever regrets you might have in your life, reading this book won't be one of them.
Includes bibliographical references and index.
Keywords: Regret